Emulating the Morals of the Prophet Muhammad in the TikTok Era: The Eradicate Sense of Shame and Modesty of Muslim Youth Based on QS. Al-Ahzab verse 21 - Ach. Zayyadi; Fawa Idatur Rizqo (al-Afkar, Journal For Islamic Studies, 2026)
Technological advancements and the increasing use of social media, particularly TikTok, have had a significant impact on the behavior of Muslim adolescents in Indonesia. While these platforms open up opportunities for creativity, they also have the potential to erode norms of modesty and weaken the sense of shame as an Islamic moral value. This study aims to analyze the interpretation of Quranic Surah Al-Ahzab verse 21 from a contemporary exegetical perspective and its relevance to the moral condition of adolescents in the digital age. The research employs a qualitative approach through a literature review using content analysis techniques on contemporary exegeses and literature related to digital culture. The results of the study confirm that Surah Al-Ahzab verse 21 not only positions the Prophet Muhammad (peace be upon him) as an ideal normative role model but also as a concrete example in upholding morality, propriety, and a sense of shame amidst modern life. The Prophet’s exemplary qualities reflected in his traits of truthfulness (shiddiq), trustworthiness (amanah), conveying the message (tabligh), and wisdom (fatonah) remain relevant as ethical guidelines for social media use. This study also indicates that the weakening of modesty and decorum among Muslim adolescents in the digital age reflects a lack of application of the moral values embodied by the Prophet Muhammad (peace be upon him). Therefore, these values must be practically applied in daily behavior, particularly in social media use. The conclusion of this study emphasizes that the application of the Prophet Muhammad’s (peace be upon him) moral values plays a crucial role in shaping the character of Muslim adolescents to be civilized, wiser, and critical of digital culture.